Video Game Art Reader Volume 3 - Funk, Tiffany (Amherst College Press, 2019)
This special edition of the VGA Reader, guest-edited by Christopher W. Totten and Enrica Lovaglio Costello, focuses on the connections between video games and architectural design. Each of the essays in this volume engages in critical investigations that reveal how game spaces evoke meaning, enhance game narratives, and explore unconventional themes.